2021
DOI: 10.1021/acs.langmuir.1c00874
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic-Inspired One-Step Strategy for Improvement of Interfacial Interactions in Cellulose Nanofibers by Modification of the Surface of Nitramine Explosives

Abstract: Recently, a burgeoning category of biocompatible botanically derived nanomaterial cellulose nanofibers (CNFs) has captured tremendous attention on account of its entangled nanostructured network, natural abundance, and outstanding mechanical properties. Biomimetically inspired by the superior properties of CNFs, this paper examined them as the coating material to cover cyclotrimethylenetrinitramine (RDX), cyclotetramethylenetetranitramine (HMX), and hexanitrohexaazaisowurtzitane (CL-20) via a facile water susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Cellulose and its derivatives are also widely used in energetic materials. Chen et al [5] examined cellulose nanofibrils as coating materials to cover cyclotrimethylenetrinitramine (RDX), cyclotetramethylene-tetranitramine (HMX), and hexanitrohexaazaisowurtzitane (CL-20) and showed the enhanced thermal stability and decreased sensitivity of those energetics. Bian et al [4] found the reduction of particle size, the improvement of thermal stability, and a decrease of impact sensitivity by more than 65 cm when RDX is combined with cellulose spheres.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellulose and its derivatives are also widely used in energetic materials. Chen et al [5] examined cellulose nanofibrils as coating materials to cover cyclotrimethylenetrinitramine (RDX), cyclotetramethylene-tetranitramine (HMX), and hexanitrohexaazaisowurtzitane (CL-20) and showed the enhanced thermal stability and decreased sensitivity of those energetics. Bian et al [4] found the reduction of particle size, the improvement of thermal stability, and a decrease of impact sensitivity by more than 65 cm when RDX is combined with cellulose spheres.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al. [5] examined cellulose nanofibrils as coating materials to cover cyclotrimethylenetrinitramine (RDX), cyclotetramethylene‐ tetranitramine (HMX), and hexanitrohexaazaisowurtzitane (CL‐20) and showed the enhanced thermal stability and decreased sensitivity of those energetics. Bian et al.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing energy density has always been the research goal of energetic materials (EMs), but the high energy and insensitive EMs are always a contradictory counterpart . To balance the high energy density, promising thermal stability, low sensitivity, and less toxicity, various inert materials, such as carbon nanotubes (CNTs), graphene oxide (GO), polydopamine (PDA), and other insensitive polymers, have been used to modify EMs . Among the currently used high-energy organic EMs, octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine (HMX), 2,4,6,8,10,12-hexanitro-2,4,6,8,10,12- hexaazaisowurtzitane (CL-20), and hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) have been widely modified using these materials to meet the requirements of space application and military weapons.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Notably, the addition of various binders can have different impacts on the thermal properties of propellants due to the inherent physicochemical features of binders and the combination of binders and other components. 33 That is to say, the potential incompatibility of the reaction or interaction between improper binders and other ingredients in propellants may accelerate the maturing process and change the thermal stability. 34 Therefore, as the energetic binder may encounter different surrounding thermal conditions during its practical application, it is essential to conduct comprehensive and indepth studies on the thermal decomposition behavior of the energetic binder.…”
Section: Introductionmentioning
confidence: 99%